Conocimiento de tradiciones culturales de Iquitos en estudiantes del primer grado de secundaria, Institución Educativa Sagrado Corazón y Mariscal Oscar Raymundo Benavides, Iquitos 2021 - Alvan Fachin, Wilma Caroline (2022)
The general objective of the research was: To establish the difference in the knowledge of the cultural traditions of Iquitos in students of the first grade of secondary school of the Educational Institution "Sagrado Corazón" and the Educational Institution "Mariscal Oscar Raymundo Benavides" of Iquitos, in the year 2021. The research was descriptive-comparative. The general design that was used was that of non-experimental research of a cross-sectional comparative descriptive type. The population was made up of 728 students from the Sagrado Corazón and Mariscal Oscar Raymundo Benavides educational institutions in the city of Iquitos in the year 2021. The sample consisted of 270 first grade high school students from educational institutions distributed as follows: 139 students from IE Sagrado Corazón and 131 from IE Mariscal Oscar R. Benavides. The data collection instrument that was used was the questionnaire whose purpose was to obtain information on the knowledge of the cultural traditions of Iquitos in students of the first grade of secondary school of the Educational Institutions "Sagrado Corazón" and "Mariscal Oscar Raymundo Benavides", from the district of Iquitos. The most important results are: tc = 0.03 < tt = 3.74, gl = 3, ? = 1, concluding that the level of knowledge of cultural traditions in first grade high school students is similar. Therefore, the research hypothesis is rejected: "There is a significant difference in the level of knowledge of the Cultural traditions of Iquitos between the students of the first grade of secondary school of the Educational Institution "Sagrado Corazón" and the Educational Institution "Mariscal Oscar Raymundo Benavides "Iquitos, in the year 2021".